2018
DOI: 10.1002/ente.201700858
|View full text |Cite
|
Sign up to set email alerts
|

3D‐Printed, Carbon‐Nanotube‐Wrapped, Thermoresponsive Polymer Spheres for Safer Lithium‐Ion Batteries

Abstract: Safety of lithium‐ion batteries (LIBs) has persistently plagued their development, despite widespread commercialization and usage. Thermal runaway is a notorious event where the overheating of the LIB results in a chain of events leading to the catastrophic failure of the device. Here, an in situ safety mechanism that shutdowns the LIB at critical temperatures before the onset of thermal runaway is developed. This is achieved by the deposition of thermal responsive polyethylene (PE) microspheres coated with mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…In addition, Yang and co-workers achieved safer LIBs by depositing CNT-wrapped thermoresponsive polyethylene microspheres on the electrodes via FDM, which can form an insulating PE film to prevent ionic flow at high temperatures, thereby rapidly causing a shutdown in the LIBs. 150 Most importantly, FDM enables the precise deposition of a minimal amount of CNT-coated PE microspheres onto electrodes, which simultaneously perform the function as a battery shutdown additive.…”
Section: Problem-oriented Designsmentioning
confidence: 99%
“…In addition, Yang and co-workers achieved safer LIBs by depositing CNT-wrapped thermoresponsive polyethylene microspheres on the electrodes via FDM, which can form an insulating PE film to prevent ionic flow at high temperatures, thereby rapidly causing a shutdown in the LIBs. 150 Most importantly, FDM enables the precise deposition of a minimal amount of CNT-coated PE microspheres onto electrodes, which simultaneously perform the function as a battery shutdown additive.…”
Section: Problem-oriented Designsmentioning
confidence: 99%
“…Carbon nanotubes (CNTs) have been widely used to manufacture different devices such as sensors, transistors, supercapacitors, and especially 3D‐printed batteries, due to their high mechanical strength, high chemical stability, large specific surface area, as well as excellent electrical and thermal properties. For instance, Kim et al reported a printed highly conductive CNT microarchitecture ( Figure a) .…”
Section: Electrode Materials For 3d‐printed Batteriesmentioning
confidence: 99%
“…However, to reduce the shutdown time to effectively prevent thermal runaway, the necessary loading of PE microspheres in the electrode shown to be 10.5 mg cm −2 , which leads to visible electrode thickness increase (>50 um) and reduction of the cell energy density. Another example of such electrode design was demonstrated in a 3D‐printable carbon nanotube (CNT) coated PE microspheres 55 as a thermal responsive layer (Figure 5(D)). The CNT‐coated PE microspheres not only exhibit improved electrical and thermal conductivity, but also greatly reduce the loading of PE microspheres required to completely shut down the cells to 1 mg cm −2 (Figure 5(B),(E)).…”
Section: Thermal Shutdown Electrodesmentioning
confidence: 99%
“…(F) Cycling profile of PE‐CNT‐printed cell demonstrating shutdown at 120°C. (reproduced with permission 55 …”
Section: Thermal Shutdown Electrodesmentioning
confidence: 99%